Critical path analysis for groundhandling activities: a case study of airbus performance at Kulap / Zarina Md Mukhtar - Md Mukhtar, Zarina (1991)
An appreciable contribution to- time saving and in particular to utilisation of the aircraft depends on the activities carried out during the aircraft on transit/turnaround. Within the present available resource of labour, equipment and materials, the minimur time must be met in accordance to the assigned tims cnofki -fi or? However, under a set of constraint, the optimisation is being made using the Critical Path Analysis method for the aircraft to achieve a more economical period of time on the ground. A saving in time can be obtained for the aircraft when compared to the traditional path stretching and holding at a longer time on the ground. From the study conducted, the aircraft transit/turnaround time can be reduced and this will maximise the aircraft utilisation and achieve ground time savings.